Perancangan Pengendalian Klaim pada Proses Pengiriman di Perusahaan Logistik - Angela Jayadi; I Nyoman Sutapa (Jurnal Titra, 2023)
Logistic Company is a freight forwarding service company that operates on bothdomestic and international scales. The services they offered include transportation by road and sea, which internally refers to as road-sea-road. In the shipping process, there are some challenges, one of them is the occurence of claims. Claims happen when the goods arrive at the recipient in damage or insufficient condition. In order to reduce the occurence of claims, the company needs to identify the causes of the claims. Method that is used in this research is the DMAIC method. Causes of claims are identified using 5 whys analysis and one of the seven tools methods, namely fishbone diagram. After being identified using 5 whys analysis and the fishbone diagram, it was found that most of the occurrences of claims are caused by human factors and the stuffing system. Therefore, a suggestion is found by creating a Key Risk Indicator (KRI) that is expected to assist the company to minimize claims.